Evaluation of the hyper‐threading technology for heat conduction‐type problems - Ivanikovas, Sergėjus; Dzemyda, Gintautas (Mathematical Modelling and Analysis, 2007)
Symmetric Multi Processor (SMP) systems become popular and available for most users nowadays. The main factor that affects the performance while working with a large amount of data with the SMP system is operating memory speed. Hyper‐Threading technology lets to increase the amount of threads working in parallel and to speed‐up the execution of program using the same hardware. A standard heat conduction problem was chosen as a benchmark to test the SMP system performance while working with memory‐intensive tasks. The results of practical tests and the quantitative estimations of efficiency are presented in the article. The experiments indicate how Hyper‐Threading technology helps to use the SMP systems and dual‐core processor systems more effectively while working with a large amount of data. First Published Online: 14 Oct 2010